1981
DOI: 10.1093/infdis/143.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Bacteriologic Efficacy of Moxalactam, Cefotaxime, Cefoperazone, and Rocephin in Experimental Bacterial Meningitis

Abstract: The pharmacokinetics and bacteriologic efficacy of four beta-lactam antibiotics were studied in the serum and cerebrospinal fluid (CSF) of rabbits using two test strains, Escherichia coli type K1 and group B Streptococcus type III, and 24 gram-positive isolates. Although moxalactam, cefotaxime, cefoperazone, and rocephin are active in vitro against gram-negative bacilli, the gram-positive bacteria Listeria monocytogenes and Streptococcus faecalis were resistant to all four drugs; group B streptococci were resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
61
2

Year Published

1982
1982
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(72 citation statements)
references
References 19 publications
9
61
2
Order By: Relevance
“…Bacteria grow slowly in CSF when compared with broth (42)2, which may interfere with the action of certain antibiotics, such as the beta lactams, maximally effective during rapid bacterial growth. In addition, the normal clearance mechanism of the CSF is operative early during experimental meningitis (43), but resistance to CSF outflow increases during experimental meningitis in rabbits (44) (25,26). These studies were of short duration; the experiments in this paper are confirmatory and extend these observations to long term (5 d) therapy and ultimate outcome (e.g., cure).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Bacteria grow slowly in CSF when compared with broth (42)2, which may interfere with the action of certain antibiotics, such as the beta lactams, maximally effective during rapid bacterial growth. In addition, the normal clearance mechanism of the CSF is operative early during experimental meningitis (43), but resistance to CSF outflow increases during experimental meningitis in rabbits (44) (25,26). These studies were of short duration; the experiments in this paper are confirmatory and extend these observations to long term (5 d) therapy and ultimate outcome (e.g., cure).…”
Section: Discussionsupporting
confidence: 59%
“…The results strongly support the conclusion that when CSF antibiotic levels exceeded the MBC for the test strain, the results of therapy were significantly better by all parameters than the results achieved with regimens that did not attain CSF antibiotic concentrations above this level. The need for bactericidal antibiotics for optimal therapy of bacterial meningitis is suggested by several lines of evidence: (a) the disease represents an infection in an area of impaired host resistance (7-9, 13, 24), and may, like bacterial endocarditis and bacteremia in the neutropenic host (15,16), require bactericidal antibiotics for cure; and (b) most studies of experimental meningitis in animals suggest that CSF antibiotic concentrations must exceed the MBC of the test strain by severalfold to achieve rapid bacterial killing in vivo (17)(18)(19)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly applicable to GBS meningitis, the most common clinical GBS syndrome. Ceftizoxime resembles other new ,B-lactams in this regard, such as moxalactam, cefoperazone, rocephin, and cefotaxime (11).…”
mentioning
confidence: 96%
“…There are no other reported series of the in vitro bactericidal efficacy of the newer cephalosporin agents against large numbers of GBS strains as is currently presented. However, ceftizoxime appears to have MBCs against nontolerant GBS comparable to those of cefotaxime, cefoperazone, and rocephin and superior to that of moxalactam (11). In a study of only nine GBS clinical isolates, Shaad et al (11) reported an MBC of cefoperazone and rocephin for 90%o of isolates of 0.25 ,ug/ml, whereas for cefotaxime it was 0.12 ,ug/ ml.…”
mentioning
confidence: 98%
See 1 more Smart Citation